Mediation Role of Satisfaction in the Influence of Experiential Marketing on Word of Mouth on Sharia Bank Customers - Rudi Yacuub; M. Iqbal (Budapest International Research and Critics University, 2022)
This study aims to determine how the mediating role of satisfaction in the influence of experiential marketing on word of mouth on Islamic bank customers. This study uses a quantitative method with a questionnaire as a research instrument. The population in this study were 130 customers of BSI KC Palembang Demang using the accidental sampling method. The results show that experiential marketing has a positive impact on satisfaction, satisfaction has a positive impact on word of mouth, and experiential marketing has a positive impact on word of mouth, and satisfaction successfully mediates experiential marketing on word of mouth.